Transformational Leadership dan Literasi AI sebagai Strategi Peningkatan Job Performance Karyawan Start-Up di Era Digital : [Transformational Leadership and AI Literacy as Strategies to Improve Job Performance of Start-Up Employees in the Digital Era] - Trifiana Tiodora; Wilson Bangun; Hendra Achmadi; Yohana Cahya Palupi Meilani (Milestone: Journal of Strategic Management, 2025)
This study aims to analyze the effect of transformational leadership and artificial intelligence (AI) literacy on job performance with AI anxiety and managing workplace FOMO as mediating variables in millennial generation employees in start-up companies. Millennial employees, who dominate the workforce in this sector, have unique characteristics such as flexible work preferences, dependence on technology, and the need for a collaborative work environment. However, they also face psychological challenges due to high work dynamics, such as anxiety about AI and the pressure to always be connected. This study uses a quantitative approach with a survey method involving millennial employees from various start-up companies in Indonesia. Data was collected through online questionnaires and analyzed using Structural Equation Modeling (SEM) to test the relationship between variables in the research model developed based on the Job Demands-Resources (JD-R) Model. The results showed that transformational leadership and AI literacy have a positive and significant effect on job performance. In addition, AI anxiety and managing workplace FOMO proved to be significant mediators, where transformational leadership and high levels of AI literacy were able to reduce anxiety about technology and stress due to digital pressure. Thus, this study provides theoretical and practical contributions in the development of leadership strategies and human resource policies, especially in improving the welfare and productivity of millennial employees in a digital technology-based work environment. Abstrak Bahasa Indonesia: Penelitian ini bertujuan untuk menganalisis pengaruh transformational leadership dan artificial intelligence (AI) literacy terhadap job performance dengan AI anxiety dan managing workplace FOMO sebagai variabel mediasi pada karyawan generasi milenial di perusahaan start-up. Karyawan milenial, yang mendominasi tenaga kerja di sektor ini, memiliki karakteristik unik seperti preferensi kerja fleksibel, ketergantungan pada teknologi, dan kebutuhan akan lingkungan kerja yang kolaboratif. Namun, mereka juga menghadapi tantangan psikologis akibat dinamika kerja yang tinggi, seperti kecemasan terhadap AI dan tekanan untuk selalu terhubung. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei yang melibatkan karyawan milenial dari berbagai perusahaan start-up di Indonesia. Data dikumpulkan melalui kuesioner online dan dianalisis menggunakan Structural Equation Modeling (SEM) untuk menguji hubungan antar variabel dalam model penelitian yang dikembangkan berdasarkan Job Demands-Resources (JD-R) Model. Hasil penelitian menunjukkan bahwa transformational leadership dan AI literacy memiliki pengaruh positif dan signifikan terhadap job performance. Selain itu, AI anxiety dan managing workplace FOMO terbukti sebagai mediator yang signifikan, di mana kepemimpinan transformatif dan tingkat literasi AI yang tinggi mampu mengurangi kecemasan terhadap teknologi serta stres akibat tekanan digital. Dengan demikian, penelitian ini memberikan kontribusi teoretis dan praktis dalam pengembangan strategi kepemimpinan dan kebijakan sumber daya manusia, khususnya dalam meningkatkan kesejahteraan dan produktivitas karyawan milenial di lingkungan kerja berbasis teknologi digital.